2016
DOI: 10.1093/jnci/djw264
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and the Transformation of Monoclonal Gammopathy of Undetermined Significance to Multiple Myeloma: A Population-Based Cohort Study

Abstract: Obesity and black race are risk factors for transformation of MGUS to MM. Future clinical trials should examine whether weight loss is a way to prevent the progression to MM in MGUS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 36 publications
1
52
0
1
Order By: Relevance
“…Although our results are limited by the small number of cases and should be interpreted with caution, the consistently high risk 42 strengthens the notion that obesity plays a role in myelomagenesis and is possibly the first identified modifiable risk factor for progression of MGUS to MM. We did not find body weight or body composition at study baseline in MGUS/LC-MGUS cases to be risk factors for progression to MM and other LP diseases.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although our results are limited by the small number of cases and should be interpreted with caution, the consistently high risk 42 strengthens the notion that obesity plays a role in myelomagenesis and is possibly the first identified modifiable risk factor for progression of MGUS to MM. We did not find body weight or body composition at study baseline in MGUS/LC-MGUS cases to be risk factors for progression to MM and other LP diseases.…”
Section: Discussionsupporting
confidence: 77%
“…A study on a cohort of US veterans within the Veterans Health Administration system found an increased risk of MM to be associated with both overweight (HR, 1.55; 95% CI, 1.16-2.06) and obesity (HR, 1.98; 95% CI, 1.47-2.68) at MGUS diagnosis. 42 We thus speculate that the observed risk of MM in individuals with obesity is not because of increased risk of MGUS, but rather that they have similar MGUS prevalence but a higher risk of progression.…”
Section: Discussionmentioning
confidence: 78%
“…Obesity has been strongly associated with precancerous lesions and conditions such as colon adenomas [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86], monoclonal gammopathy [87][88][89][90][91][92][93][94][95][96][97][98], chronic pancreatitis [99][100][101][102], or inflammatory bowel disease (IBD) [103][104][105][106]. Observed risks of cancers associated with obesity include breast [107][108][109][110][111], colorectal [112][113][114][115], pancreatic [99]…”
Section: Morbid Obesitymentioning
confidence: 99%
“…The shortening of the latent period from benign to malignant disease in association with obesity has been most clearly demonstrated at the clinical level, where disease-associated monoclonal immunoglobulin provides a biomarker for early detection and demonstration that obesity accelerates the conversion of monoclonal gammopathy of unknown significance (MGUS) to multiple myeloma (MM) (29). In further support of this proposal that obesity does not initiate but rather promotes cancer progression, almost all murine models in which obesogenic diets and DIO promote tumors require experimental utilization of genetically modified animals containing cancer-predisposing genes or transplantation of preexisting tumor cell lines (5,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Systems Demonstrating That Obesity Promotes and Accelerates mentioning
confidence: 99%